2011
DOI: 10.1055/s-0030-1256413
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic submucosal dissection in a European setting. A multi-institutional report of a technique in development

Abstract: In this early experience, the feasibility of ESD appeared to be good but R0 resection and complication rates did not match those reported by Japanese authors and must be improved by an extended practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
94
2
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(114 citation statements)
references
References 16 publications
12
94
2
6
Order By: Relevance
“…En bloc resection rate in colon ESD has been reported about above 90% in Japan (14-16), 70% in Europe (17). In our multicenter study, the en bloc resection rate was 83.8%, similar to Japanese study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…En bloc resection rate in colon ESD has been reported about above 90% in Japan (14-16), 70% in Europe (17). In our multicenter study, the en bloc resection rate was 83.8%, similar to Japanese study.…”
Section: Discussionsupporting
confidence: 86%
“…The lesions for which en bloc resection could not be achieved located in right colon/transverse colon 17 …”
Section: Curabilitymentioning
confidence: 99%
“…It must be said that ESD might overcome this limitation, defining submucosal involvement more precisely. Nevertheless, ESD is rarely performed in Europe as it is considered technically challenging, while it is affected by a consistent rate of complications (29.2 %) and allows a rate of R0 resections of no more than 72.9 % of cases [22]. Considering our data, it would be advisable to resect rectal polyps >2 cm directly by TEM, in order to obtain a correct T stage and possibly a radical minimally invasive treatment.…”
Section: Discussionmentioning
confidence: 91%
“…Other countries in East Asia (e.g., Korea) that have the highest incidence rates of gastric cancer have also obtained almost similarly favorable ESD outcomes (22)(23)(24). In contrast, some investigators from Western countries have reported poor feasibility and a relatively high postoperative complication rate for ESD, probably because these countries have lesser opportunities for acquiring technical skills for performing ESD due to the lower incidence rates of gastric cancer (25)(26)(27). Thus, in order to introduce and standardize ESD in regions where ESD is still in the developmental stage (e.g., European countries), it is necessary to establish an effective training system for ESD in addition to introducing the several advances of ESD (17,18,28,29).…”
Section: Discussionmentioning
confidence: 99%